Left atrial strain determinants across heart failure stages; insight from MASCOT registry. (4th February 2022) - Benfari, G; Mandoli, GE; Magne, J; Miglioranza, M; Ancona, R; Reskovic Luksic, V; Pastore, MC; Santoro, C; Michalski, B; Muraru, D; Donal, E; Cosyns, B; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. OnBehalf: MASCOT investigators Background: Few studies analyzed left atrial (LA) peak atrial longitudinal strain (PALS) determinants, particularly across heart failure (HF) stages. We aimed to analyze the pathophysiological and clinical PALS correlates in a large international prospective registry. Methods: This is a multicenter prospective observational study enrolling 745 patients with HF stages 0-C from July to October 2018. Data included PALS and left ventricular global longitudinal strain (LV-GLS). Exclusion criteria were: valvular prosthesis; atrial fibrillation; cardiac transplantation; poor acoustic window. Results: Median global PALS was 17% [24-32]. 29% of patients were in HF-stage 0/A, 35% in stage-B, and 36% in stage-C. Together with age, the echocardiographic determinants of PALS were LA volume and LV-GLS (overall model R²=0.50, p < 0.0001). LV-GLS had the strongest association with PALS at multivariable analysis (beta:-3.60 ± 0.20, p < 0.0001). Among HF-stages (Figure 1), LV-GLS remained the most important PALS predictor (p < 0.0001) whereas age was only associated with PALS in lower HF-stage 0/A or B (R=-0.26 p < 0.0001, R=-0.23 p = 0.0001). LA volume increased its association to PALS moving from stage 0-A (R=-0.11; P = 0.1) to C (R=-0.42; P < 0.0001). PALS was the single most potent echocardiographic parameter in predicting HF stage (AUC for B vs. 0/A 0.81, and AUC vs. 0/A for C 0.76). PALS remained independently associated with HF stages after adjusting for ejection fraction, E/e' ratio and mitral regurgitation grade (p < 0.0001). Conclusion: Although influenced by LV-GLS and LA size across HF-stages, PALS is incrementally and independently associated with clinical status. LA function may reflect a substantial part of the hemodynamic consequences of ventricular dysfunction.